2021
DOI: 10.1002/dta.3017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood parameters by linear discriminant models for the detection of testosterone administration

Abstract: The steroidal module of the Athlete Biological Passport (ABP) has been used since 2014 for the longitudinal monitoring of urinary testosterone and its metabolites to identify samples suspicious for the use of synthetic forms of Endogenous Anabolic Androgenic Steroids (EAAS). Multiple recent studies have suggested that monitoring of blood parameters may provide enhanced detectability of exogenous testosterone administration. Transdermal and intramuscular testosterone administration studies were carried out in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…81 A discriminant analysis of transdermal T gel administration to 15 healthy men reported that reticulocyte parameters that exceeded cutoff thresholds in only 7/32 treatment sequences. 82 The present study extending these findings to healthy females treated daily for 7 days with transdermal T gel reveals better differentiation of exogenous T exposure using more sensitive reticulocyte parameters alone as well as when combined with steroidal module parameters. Further placebo-controlled studies of longer duration are required to determine the optimal algorithm incorporating both steroid and hematological profiles to detect T doping in women with wider detection windows.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…81 A discriminant analysis of transdermal T gel administration to 15 healthy men reported that reticulocyte parameters that exceeded cutoff thresholds in only 7/32 treatment sequences. 82 The present study extending these findings to healthy females treated daily for 7 days with transdermal T gel reveals better differentiation of exogenous T exposure using more sensitive reticulocyte parameters alone as well as when combined with steroidal module parameters. Further placebo-controlled studies of longer duration are required to determine the optimal algorithm incorporating both steroid and hematological profiles to detect T doping in women with wider detection windows.…”
Section: Discussionsupporting
confidence: 57%
“…37 Using a more limited set of reticulocyte parameters (% reticulocytes, immature reticulocyte fraction) than in the present study, the effects of injectable T were much more prominent than those of transdermal administration. 82 Following injections of 250-mg mixed T esters, the urine steroid module markers (T/E ratio 5α-diol/E ratio) were positive in 9/12 men, whereas the key hematological parameters (% reticulocytes, OFF score and ABPS) were positive in fewer (three to six) participants. 81 A discriminant analysis of transdermal T gel administration to 15 healthy men reported that reticulocyte parameters that exceeded cutoff thresholds in only 7/32 treatment sequences.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations